Extracellular Vesicles: Potential Roles in Regenerative Medicine - De Jong, Olivier G.; Van Balkom, Bas W. M.; Schiffelers, Raymond M.; Bouten, Carlijn V. C.; Verhaar, Marianne C. (Frontiers in Immunology, 2014)
Extracellular vesicles (EV) consist of exosomes, which are released upon fusion of the multivesicular body with the cell membrane, and microvesicles, which are released directly from the cell membrane. EV can mediate cell-cell communication and are involved in many processes, including immune signaling, angiogenesis, stress response, senescence, proliferation, and cell differentiation. The vast amount of processes that EV are involved in and the versatility of manner in which they can influence the behavior of recipient cells make EV an interesting source for both therapeutic and diagnostic applications. Successes in the fields of tumor biology and immunology sparked the exploration of the potential of EV in the field of regenerative medicine. Indeed, EV are involved in restoring tissue and organ damage, and may partially explain the paracrine effects observed in stem cell based therapeutic approaches. The function and content of EV may also harbor information that can be used in tissue engineering, in which paracrine signaling is employed to modulate cell recruitment, differentiation, and proliferation. In this review, we discuss the function and role of EV in regenerative medicine and elaborate on potential applications in tissue engineering.